Students’ perspective on absenteeism: a cross-sectional study among students at government medical colleges of Western Maharashtra - Narayankar, Shilpa L.; Jadhavar, Suraj T.; Patil, Saurabh S.; Gode, Nikhil R.; Kinake, Megha S.; Thokal, Mansi S.; Dhande, Sayli S. (International Journal of Research in Medical Sciences, 2024)
Background: The professional courses as undergraduate medical education need high theoretical and clinical classes attendance as those students will be future doctors and will deal with the health and disease of the public. In spite of implementing strict policies regarding student attendance, the rate of absenteeism in medical colleges remains high and is a growing apprehension a phenomenon that is also on the rise in universities worldwide. Methods: A cross-sectional study in few Governments Medical Colleges of Western region of Maharashtra using a self-administered questionnaire. Data was collected and analysed through Google forms. Results: Preparatory leave before every examination required (50.7%), air-conditioned classrooms (49.7%), good ventilated classrooms (44.1%), interactive teachers (41.8%), decrease lecture duration (38%), more practical less theory classes (37.6%) and good transportation facilities (34.3%) were various major suggestions given by students to increase the overall attendance. Conclusions: Feedback from students must be repeatedly considered while designing and revising the curriculum to reduce absenteeism.